Mindray BC‐6800 body fluid mode, performance of nucleated cells, and differential count in ascitic and pleural fluids. (7th November 2015) - Buoro, S.; Mecca, T.; Azzarà, G.; Seghezzi, M.; Candiago, E.; Gianatti, A.; Crippa, A.; La Gioia, A.
Summary: Introduction: An accurate and rapid analysis of cells in body fluids (BFs) is important for diagnosis and follow‐up in many pathological conditions. We evaluated the analytical performance of the module BF Mindray BC‐6800 (BC‐6800‐BF) for cytometric analysis of ascitic and pleural fluids. Methods: A total of 99 ascitic and 45 pleural samples were collected and assessed with BC‐6800‐BF and optical microscopy. This study also includes the evaluation of limit blank (LoB), limit detection (LoD), limit quantitation, (LoQ), carryover, linearity, and diagnostic concordance between the two methods. Results: For TC‐BF, LoB was 1 × 10 6 cells/L, LoD was 3 × 10 6 cells/L, and LoQ was 4 × 10 6 cells/L. Linearity was excellent ( r 2 = 0.99) and carryover was negligible. TC‐BF performed with the two methods showed Pearson's correlation of 0.99 ( P < 0.0001), Passing–Bablok regression y = 1.04 x − 1.17, and bias 33.7 cells. In ascitic fluids, polymorphonuclear cells (PMN) showed an area under curve (AUC) of 0.98 ( P < 0.0001). In pleural fluids, mononuclear cells (MN) and PMN % displayed an AUC of 0.79 ( P < 0.0001) and 0.93 ( P < 0.0001), respectively. Conclusions: BC‐6800‐BF in ascitic and pleural fluids offers rapid and accurate cell and differential counts in clinically relevant concentration ranges. The use of BC‐6800‐BF may allow to replace routine optical counting, except for samples displaying abnormal cell counts or abnormal DIFF scattergram.